Meningkatkan Kreativitas Anak Usia 5-6 Tahun melalui Media Loose Part di TK IT Abatatsa Kabupaten Pasuruan - Nadia Kaffiya Salsabila; Naila Naila; Indriana W (AS-SABIQUN, 2022)
Every child has a natural creativity. Children's creativity can be developed, because it needs to be developed from an early age. Stimulation and stimulation is one of the factors to develop creativity. Now many children learn who are still racing on the teacher waiting to give an example, so that children cannot develop their imagination. The loose parts method is a method that uses materials around us, which can be removed and installed, not disposable, can be assembled according to the wishes or creativity of the child. This research is a CAR classroom action research. The research subject is the children of group B TK IT ABATATSA PASURUAN. The results of the study using loose parts showed that the media increased creativity in early childhood. When children are given the freedom to do direct exploration of the environment, they can enrich creative ideas, raise curiosity in children, and imagination ideas. So that learning that initially relies on the teacher to give examples, is monotonous and boring, will become more fun and develop children's ideas.